Pesan Moral Dalam Lirik Lagu Mangku Purel Karya Nur Bayan: Indonesia - Ardiansyah, Muhammad; Hariyanto, Didik (Jurnal Ilmu Komunikasi, 2023)
ABSTRACT Song Mangku Purel by Nur Bayan became the song that was most popular with singers and occupied the first trending position on YouTube in November 2022. There are positive and negative comments about the song. This research aims to find out the moral message that is in the lyrics of the song Mangku Purel Karya Nur Bayan. The study used a qualitative approach with observational data collection techniques, listening to Mangku Purel's song on the YouTube video "Henny Adella" and documenting it by recording the lyrics of her song. Then the lyrics of the song were analyzed using the semiotic approach of Charles Sanders Pierce. The results of this study show that there are some words or sentences in the Mangku Purel song that do not reflect the moral message, but there are still sentences that match the moral message. The conclusion obtained in this research is that in the song Mangku Purel by Nur Bayan, there is a word or sentence that connotes negative, tends to represent the asylum action to describe the asyllum action specifically, sounds rough and vulgar, but in the song still contains a moral message in the form of an adjudication to stop doing asylums, urges to be the head of the tanga house who is responsible, and urges not to deny the promise. Keywords: Moral Message; Lyrics of song; Mangku Purel;Semiotic; Charles Sanders Pierce